Troubled Knowledge: Land, Race, and Logics of Extraction in Alberta’s Tar Sands - Spady, Samantha (2020)
This dissertation examines how tar-sands extraction comes to be seen as normal and an inevitable consequence of present-day lifestyles. The research is built from interviews with 30 white oil-industry workers involved in oil-extraction projects in the Athabasca tar-sands deposit. The ways in which oil has shaped economic and social relations not only in Fort McMurray, AB, but in the Canadian state generally are significant to unravel and examine. This study attempts to capture the ways that tar sands are made possible through state policy, investment, and economic structuring, as well as how these things are experienced at the level of the individual. I analyze the logics, and rationales used to justify continued extraction in this region, and I work to debunk them and also to understand how and why they are so powerful. Furthermore, I contrast the ways in which oil extraction comes to make sense to itself, besides the ways in which Indigenous people have demonstrated this logic to be limited and, in many cases, untrue. I work through these different ways of relating to—and understanding—oil, in order to contrast the different worlds that are competing in this place. Ph.D.